Comprehensive Evaluation of Physical, Nutritional, and Sensory Properties of Gluten–Free Instant Banana Brownie Mix - Balapuwaduge Harshani Kaushalya Mendis; Maneesha Hansani Kodikara; Harshaka Maduwantha Jans; Perumpuli Arachchige Buddhika Niroshie Perumpuli; Ganwarige Sumali Nivanthi Fernando (Food ScienTech Journal, 2025)
The increasing demand for Gluten-free products has spurred interest in utilising underutilized agricultural resources such as banana flour, which also offers sustainable solutions in managing post-harvest loss. The study focused on developing a gluten-free instant brownie mix using banana flour from three varieties, namely Ambul, Seni, and Cavendish, and to analyse their physicochemical, functional, nutritional, and sensory properties. The developed brownie mix was assessed for its proximate composition, revealing a balanced nutritional profile with a notable level of dietary fibre (5.75±0.08 g/100 g) and is an energy-dense product with higher carbohydrate content (86.87±0.76 g/100 g) and lower fat content (4.50 ± 0.71 g/100 g). Highlighting higher water absorption (106.0 ± 2.83%) and oil absorption capacities (225.50 ± 0.71 %) helped to enhance the brownie’s texture and moisture, especially when gluten-free. The Kraft paper zip lock packaging showed higher moisture content (3.5±0.1 g/100 g) and titratable acidity (0.00095±0.0001%) compared to high-density polyethylene packaging after nine weeks of shelf-life testing for developed brownie. The Kraft paper zip lock packaging showed higher moisture content (3.5±0.1 g/100 g) and titratable acidity (0.00095±0.0001%) compared to high-density polyethylene packaging after nine weeks of shelf-life testing. Banana brownies contain a higher carbohydrate content (5.75 ± 0.08 g/100 g), along with a notable fibre content (5.75 ± 0.08 g/100 g). In addition to promoting resource efficiency and reducing post-harvest losses, this research demonstrates the industrial potential of banana flour in developing sustainable Gluten-free bakery products.